PENGARUH REKRUTMEN DAN PELATIHAN TERHADAP PENINGKATAN KOMPETENSI PANITIA PEMILIHAN KECAMATAN DI KABUPATEN HULU SUNGAI UTARA - Mohammad Noor (Jurnal PubBis, 2018)
In enforcement of elections and Pilkada, there are often electoral disputes that have an impact on election complaints of election participants. The object of the election result disputes is inconsistency between the election result report by the KPPS officers with the Determination of Election Vote Result by the National Election Commission. In order to avoid any errors in the selection process described above, the Nation Election Commission in Hulu Sungai Utara District has made a breakthrough in the form of selective recruitment and management training model for increasing the more professional organizers competence. Based on the research has been done, there is a significant correlation related to the improvement of competence as the impact of implementation of selective recruitment process and model of management training of election. Research conducted by questionnaire method to respondents and analyzed by application program of SPSS (Statistical Packages of Social Science).